ANALISIS HARGA EMAS DI INDONESIA (Studi Empiris Tahun 1996-2020) - Lastri, Lastri (Jurnal Manajemen dan Bisnis, 2021)
Gold is a profitable investment from other types of investment. The price of gold in Indonesia increases every year. This is caused by several factors, namely US Dollar exchange rate, deposit interest rate, inflation, GDP per capita, and gold production. The Data used is time series data from 1990 – 2020 which are from Bank Indonesia, Kementerian Perdagangan, BPS Indonesia dan Gold Price. The research method is multiple linear regression. The result showed by partial test (t-test) that US Dollar exchange rate has a negative effect not significant on the price of gold, deposit interest rate has a significant negative effect on the price of gold, inflation has a positive effect not significant on the price of gold, GDP per capita has a significant positive effect on the price of gold, and the production of gold has a significant positive effect on the price of gold. For F-test US Dollar exchange rate, deposit interest rate, inflation, GDP per capita, and gold production has a significant effect on the price of gold. The Coefficient of Determination (R2) can be said that variance price of gold is 97,4% explained by US Dollar exchange rate, deposit interest rate, inflation, GDP per capita, gold production and the remaining is 2,6% explained by the other variables outside the research model such as Indonesia Composite Index (ICI), World Crude Oil Prices and the others.